If 1 , α 1 , α 2 , α 3 , α 4 are fifth roots of unity, and
i = 1 ∑ 4 2 − α i 1 = b a
Where a and b are coprime integers then find a − b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great way of obtaining the (general) formula. I do have a preference for transforming the roots of the equation as a way of evaluating such sums, since it tends to be much more direct and there is fewer "forcing" of manipulations.
I think this general formula wont work when a=1, @Otto Bretscher
Log in to reply
That's why I'm saying "where a fails to be a root of unity." For roots of unity, including 1, both sides of the equation are undefined.
Log in to reply
Oh right. Missed it. Actually I solved the same question with a=1 instead of 2 which took a long time since this method was not applicable and had to resort to calculus.
Log in to reply
@Sanchit Aggarwal – In the case a = 1 , you can substitute w = x x − 1 into w n − 1 + w n − 2 + . . . . + w + 1 to find n x n − 1 − 2 n ( n − 1 ) x n − 2 . . . , and the sum (excluding w = 1 ) will be 2 n − 1 .
Simple & elegant......love it, Sir Otto!!
We have that, f ( x ) = x 5 − 1 = ( x − 1 ) ( i = 1 ∏ 4 ( x − α i ) ) ⟹ ln ( f ( x ) ) = ln ( x − 1 ) + i = 1 ∑ 4 ( ln ( x − α i ) ) ⟹ d x d ln ( f ( x ) ) = x − 1 1 + i = 1 ∑ 4 ( x − α i 1 ) ⟹ f ( x ) 1 × f ′ ( x ) = x − 1 1 + i = 1 ∑ 4 ( x − α i 1 ) Now,just put x = 2 , f ( 2 ) 1 × f ′ ( 2 ) = 1 + Required expression f ( 2 ) = 3 1 , f ′ ( x ) = 5 x 4 = 8 0 ⟹ Required expression = 3 1 8 0 − 1 = 3 1 4 9 ⟹ Answer = 1 8 And done!
That is a reasonable approach. However, do you know to what extent your manipulations are valid for complex numbers? IE Could we take lo g i and get a single value?
Well, this sure is one complicated way of doing things. But nice solution nonetheless.
L e t θ = 5 2 π . ∴ α n = e i ∗ 5 2 π ∗ n = C o s ( θ ∗ n ) + i S i n ( θ ∗ n ) . . . n = 1 , 2 , 3 , 4 C o s ( θ ∗ 4 ) = C o s ( − θ ∗ 4 ) = C o s ( θ ∗ 1 ) = 4 5 − 1 . C o s ( θ ∗ 3 ) = C o s ( − θ ∗ 3 ) = C o s ( θ ∗ 2 ) = − 4 5 + 1 . S i n ( θ ∗ 1 ) + S i n ( θ ∗ 4 ) = 0 . S i n ( θ ∗ 2 ) + S i n ( θ ∗ 3 ) = 0 . 2 − α n 1 = 2 − ( C o s ( θ ∗ n ) + i S i n ( θ ∗ n ) ) 1 R a t i o n a l i z i n g , = ( 2 − C o s ( θ ∗ n ) ) 2 − ( i S i n θ ∗ n ) 2 ( 2 − C o s ( θ ∗ n ) ) − i S i n ( θ ∗ n ) = 5 − 4 ∗ C o s ( θ ∗ n ) ( 2 − C o s ( θ ∗ n ) ) − i S i n ( θ ∗ n ) ∴ 2 − α 1 1 = 2 − ( C o s ( θ ∗ 1 ) + i S i n ( θ ∗ 1 ) ) 1 = 5 − 4 ∗ 4 5 − 1 ( 2 − 4 5 − 1 ) − i S i n ( θ ∗ 1 ) = 6 − 5 4 9 − 5 − i S i n ( θ ∗ 1 ) ∴ 2 − α 4 1 = 2 − ( C o s ( θ ∗ 4 ) + i S i n ( θ ∗ 4 ) ) 1 = 5 − 4 ∗ 4 5 − 1 ( 2 − 4 5 − 1 ) − i S i n ( θ ∗ 4 ) = 6 − 5 4 9 − 5 − i S i n ( θ ∗ 4 ) ∴ 2 − α 1 1 + 2 − α 4 1 = 6 − 5 4 9 − 5 − i S i n ( θ ∗ 1 ) + 4 9 − 5 − i S i n ( θ ∗ 4 ) = 2 1 ∗ { 6 − 5 9 − 5 } S i m i l a r l y 2 − α 2 1 + 2 − α 3 1 = 2 ∗ 5 − { − ( 5 + 1 ) } 2 − ( − 4 5 + 1 ) = 2 1 ∗ 6 + 5 9 + 5 . ∴ n = 1 ∑ 4 2 − α n 1 = 2 1 ∗ { 6 − 5 9 − 5 + 6 + 5 9 + 5 } = 2 1 ∗ { 3 6 − 5 5 4 − 5 − 3 5 + 5 4 − 5 + 3 5 } = 3 1 4 9 = b a . a − b = 1 8 .
Let f ( x ) = x 5 − 1 = ( x − 1 ) ∏ i = 1 4 ( x − a i )
Also,
g ( x ) = f ( x + 2 ) = ( x + 2 ) 5 − 1 = ( x − ( 1 − 2 ) ) ∏ i = 1 4 ( x − ( a i − 2 ) )
Therefore,
g ( x 1 ) = ( x 1 + 2 ) 5 − 1 = ( x 1 − ( 1 − 2 ) ) ∏ i = 1 4 ( x 1 − ( a i − 2 ) )
Now we can see roots of g ( x 1 ) are − 1 , a i − 2 1 for i = 1 , 2 , 3 , 4 .
Also,
( x 1 + 2 ) 5 − 1 = ( x 1 + 2 x ) 5 − 1 = x 5 ( 1 + 2 x ) 5 − x 5
Therefore, g ( x 1 ) = 0 = x 5 ( 1 + 2 x ) 5 − x 5
⇒ ( 1 + 2 x ) 5 − x 5 = 0
Therefore, g ( x 1 ) = ( 2 5 − 1 ) x 5 + 5 × 2 4 x 4 + something
So sum of roots of g ( x 1 ) is − 1 + ∑ i = 1 4 a i − 2 1 = ( 2 5 − 1 ) − 5 × 2 4 = 3 1 − 8 0
⇒ ∑ i = 1 4 a i − 2 1 = 3 1 − 4 9 ⇒ ∑ i = 1 4 2 − a i 1 = 3 1 4 9
Therefore, a − b = 1 8 .
All the roots are of the equation x5 – 1 = 0 Σ α = Σ αβ= Σ α βγ =Σ α β γδ= 0 Πα = 1
Let α5 = 1 so, Σ {1/(2- α i)} numerator is, 24 – (α2 + α3 + α4 + α5) 23 +…….. = 5.24 –(α1+ α2 + α3 + α4 + α5) 4.23 +…….. = 5.24 = 80 denominator is, Π(2 - α i) = 2^5 – 1 = 31 as Π (x - α i)=x^5 – 1
so a/b = (80/31) – 1/(2-1) = 49/31 a-b = 49 – 31 = 18
In the original sum was taken x instead of two. Let x be such that x^5-1=0. The sum requested is equal to (4x^3+3x^2+2x+1)(x-1)/(x^5 - 1) with x different from one. For " x = 2", we get the sum equal to 49/31, so a-b=18.
If we note that 2 1 ∣ α i ∣ = 2 1 then we can write
2 − α i 1 = 2 1 ( 1 + 2 α i + ( 2 α i ) 2 + . . . )
If we sum the above equation 'column-wise' from i = 1 to i = 5 and use that 1 + α 1 + . . . + α 4 = 0 , and that ( α 1 ) 2 = α 2 , ( α 1 ) 3 = α 3 , etc. then
2 − 1 1 + ∑ i = 1 4 2 − α i 1 = 2 1 ( 1 + 2 5 5 + 2 1 0 5 + . . . )
The RHS is a geometric series and hence by summing it and subtracting 1 from both sides we get our desired sum is 3 1 4 9
Problem Loading...
Note Loading...
Set Loading...
We can derive the formula w ∑ a − w 1 = a n − 1 n a n − 1 for the n th roots of unity w , where a fails to be an n th root of unity. Let n = 5 and a = 2 to obtain the required value 1 8 (subtract 1 since the problem starts the count at k = 1 )
To derive the formula, we make the substitution x = a − w 1 or w = x a x − 1 . Then w n = 1 gives ( a x − 1 ) n = x n or ( a n − 1 ) x n − n a n − 1 x n − 1 + . . . = 0 , and our formula follows from Viete's rule, by finding the sum of roots of the transformed equation.